HTC- May Survive in Bipolar World - Singh, Netra Pal (Industrija, 2016)
The core assets of HTC are people, innovations, and technology. But in the recent quarters, HTC has started retrenching people even from R&D divisions which are responsible for innovation and developing new technologies. It means HTC’s core assets are depleting. HTC was known for its cutting edge technology of 16mp camera and high speed '4G' technology but performing badly in the last two and half year. Why is it so? Paper objectives are to identify reasons for its downfall of HTC, distress signals for HTC downfall, and possible revival strategies for survival of HTC in Bipolar world (Samsung and Apple) of smartphones makers. In addition, research paper, paper present eight research proposition/ questions with respect to present state of HTC and its future and possible answers to these research propositions/ questions. Research paper ends with concluding remarks in the context of HTC future.
Keywords: Smartphone; Bipolar World; Cutting edge technology; Innovation; Window; Android; HTC; Technology